The identity of Damatris pudica and typification of Arctotis breviscapa (Asteraceae, Arctotideae) - Mckenzie, Robert James; Barker, Nigel P. (Phytotaxa, 2013)
The Arctotidinae, a subtribe of the Arctotideae, comprises approximately 90–100 species predominantly confined to southern and eastern Africa. The species are presently classified into five genera: Arctotheca Vaillant (1754: 604), Arctotis Linnaeus (1753: 922), Cymbonotus Cassini (1825: 397), Dymondia Compton (1953: 110) and Haplocarpha Lessing (1831: 90) (Karis et al. 2009). Cassini (1817) published the genus Damatris Cassini (1817: 139) and described a single species, D. pudica Cassini (1817: 140), for a species of Arctotidinae collected from ‘le Cap de Bonne-Espérance’ (Cape of Good Hope, South Africa). Cassini (1819) stated that Damatris pudica was described from material in the Herbier de Jussieu (P-JU). However, the identity of Damatris pudica has always been uncertain. Initially, most authors listed the genus as either poorly known or of dubious status (e.g. Lessing 1832, Candolle 1838b, Harvey 1865). Bentham (1873) tentatively considered that Damatris might be congeneric with Haplocarpha and subsequently Beauverd (1915) made the combination for D. pudica in Haplocarpha without comment on the species’ identity (although marked with a question mark to indicate a degree of uncertainty). In the most recent monograph of Arctotidinae, Lewin (1922) followed Bentham in citing Damatris as a synonym of Haplocarpha but curiously did not cite D. pudica, either as an accepted species or in the synonymy of another species. Damatris has nomenclatural priority over Haplocarpha, therefore resolution of the identity of D. pudica may have nomenclatural implications for the generic taxonomy of Arctotidinae.